Study of aluminum nitride formation by superfine aluminum powder combustion in air; Journal of the European Ceramic Society; Vol. 24, iss. 9 - Gromov А. Alexander (2004, 2004)
An experimental study on the combustion of superfine aluminum powders (average particle diameter as0.1 μm) in air is reported. Formation of aluminum nitride during combustion of aluminum in air is focused in this study. Superfine aluminum powders were produced by wire electrical explosion (WEE) method. Such superfine aluminum powder is stable in air but, if ignited, it can burn in self-sustaining way. During the combustion, temperature was measured and actual burning process was recorded by a video camera. SEM, XRD, TG-DTA and chemical analysis were executed on initial powders and final products. It was found that powders, ignited by local heating, burned in two-stage self-propagating regime. The products of the first stage consisted of unreacted aluminum (70 mass %) and amorphous oxides with trace of AlN. After the second stage AlN content exceeded 50 mass % and residual Al content decreased to 10 mass%. A qualitative discussion is given on the probable mechanism of AlN formation in air